2017
DOI: 10.1038/s41598-017-09260-8
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus infection triggered immune responses and host-pathogen cross-talks in groundnut during in-vitro seed colonization

Abstract: Aflatoxin contamination, caused by fungal pathogen Aspergillus flavus, is a major quality and health problem delimiting the trade and consumption of groundnut (Arachis hypogaea L.) worldwide. RNA-seq approach was deployed to understand the host-pathogen interaction by identifying differentially expressed genes (DEGs) for resistance to in-vitro seed colonization (IVSC) at four critical stages after inoculation in J 11 (resistant) and JL 24 (susceptible) genotypes of groundnut. About 1,344.04 million sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 78 publications
(63 reference statements)
1
63
0
Order By: Relevance
“…The genetic yield potential of peanut cultivars has been continuously challenged by several diseases including early leaf spot (ELS) caused by Cercospora arachidicola, late leaf spot (LLS) caused by Cercosporidium personatum and Tomato spotted wilt virus (TSWV). These foliar diseases cause yield losses of up to 70%, resulting in approximately $600 million in losses (Food and Agriculture Organization (FAO), 2004;Ogwulumba et al, 2008). While insecticides and fungicides have been used as part of an integrated pest management approach, breeding disease-resistant cultivars with high yield and good agronomic performance is the most economical and sustainable solution (Guo et al, 2013;Pandey et al, 2012;Varshney et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic yield potential of peanut cultivars has been continuously challenged by several diseases including early leaf spot (ELS) caused by Cercospora arachidicola, late leaf spot (LLS) caused by Cercosporidium personatum and Tomato spotted wilt virus (TSWV). These foliar diseases cause yield losses of up to 70%, resulting in approximately $600 million in losses (Food and Agriculture Organization (FAO), 2004;Ogwulumba et al, 2008). While insecticides and fungicides have been used as part of an integrated pest management approach, breeding disease-resistant cultivars with high yield and good agronomic performance is the most economical and sustainable solution (Guo et al, 2013;Pandey et al, 2012;Varshney et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Hwang also reported that the higher PAL gene expression and activity were responsible for attenuating pathogen infection in pepper as a result of signaling H 2 O 2 accumulation, generated by higher NADPH oxidase gene expression, resulting in higher endogenous SA accumulation and higher PR1 gene expression. Nayak et al . also reported that the promotion of PAL enzyme activity and higher endogenous SA accumulation, resulting in higher PRs gene expression, accompanied by higher ROS scavenging system activity, was responsible for higher resistance of groundnut to A. flavus infection.…”
Section: Resultsmentioning
confidence: 98%
“…38,39 Kim and Hwang 40 also reported that the higher PAL gene expression and activity were responsible for attenuating pathogen infection in pepper as a result of signaling H 2 O 2 accumulation, generated by higher NADPH oxidase gene expression, resulting in higher endogenous SA accumulation and higher PR1 gene expression. Nayak et al 41 also reported that the promotion of PAL enzyme activity and higher endogenous SA accumulation, resulting in higher PRs gene expression, accompanied by higher ROS scavenging system activity, was responsible for higher resistance of groundnut to A. flavus infection. Li et al 39 reported that enhancing resistance to brown rot caused by Monilinia fructicola in peach fruits by NO treatment may originate from the promotion of PAL, 4CL, C4H, CHS, and CHI gene expression and enzyme activity, resulting in higher phenol, flavonoid, and anthocyanin accumulation exhibiting antifungal capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Modern approaches such as RNA-seq have been used to identify host resistance associated pathways in different crops including maize and groundnut. For instance, in case of groundnut, an integrated IVSC and RNA-seq approach that analyzed the four different stages of infected seed samples from J11 (resistant) and JL24 (susceptible) identified 4,445 differentially expressed unigenes (DEGs) that were involved in multiple pathways such as defense-related, PR or metabolic pathway targeting genes provided a more solid understanding of cross-talk between host-pathogen interactions (Nayak et al, 2017). Likewise, an RNA-seq-based approach was deployed in groundnut to identify genes that confer resistance during PAC (Clevenger et al, 2016).…”
Section: Identification Of Candidate Genesmentioning
confidence: 99%
“…In groundnut and maize, cross-talk communication between the pathogen and host plant is the first critical step toward the rapid activation of defense mechanisms in host plants. Functional and biological composition of resistance mechanisms in maize and groundnut using integrated approaches have led to the elucidation of the roles of several genes, PR-10, chitinase, 14-kDa trypsin inhibitor, zeatin and beta-1,3-glucanase, lipoxygenase, ROS, and stress responsive proteins (such as late embryogenesis abundant protein (LEA14), catalase, glutathione S-transferase, superoxide dismutase, heat shock proteins) which play a vital role in regulating resistance and in cross-kingdom interactions between host plants and Aspergillus species in groundnut (Luo et al, 2005;Chadha and Das, 2006;Liang et al, 2006;Wang et al, 2010;Guo et al, 2011;Kumari et al, 2011;Nayak et al, 2017) and maize (Guo et al, 1997;Chen et al, 1998Chen et al, , 1999Chen et al, , 2001Chen et al, , 2002Chen et al, , 2004bChen et al, , 2006Chen et al, , 2007Chen et al, , 2012Lozovaya et al, 1998;Ji et al, 2000;Moore et al, 2004;Magbanua et al, 2007;Pechanova et al, 2011;Pegoraro et al, 2011;Roze et al, 2013;Fountain et al, 2014Fountain et al, , 2016Hawkins et al, 2015;Ogunola et al, 2017).…”
Section: Managing Aflatoxin Contamination: Similarities Between Grounmentioning
confidence: 99%